Evaluation of the Montreal Cognitive Assessment as a screening tool for cognitive dysfunction in SLE - Eric Morand; Alberta Hoi; Sudha Raghunath; Julie C Stout; Yifat Glikmann-Johnston (Lupus Science and Medicine)
Objectives Cognitive dysfunction in SLE is common and associated with significant morbidity but is currently underdetected. Early detection requires the use of screening tests, as formal diagnostic cognitive testing is time-consuming. This study aims to evaluate the Montreal Cognitive Assessment (MoCA) as a screening tool for cognitive dysfunction in SLE.Methods Patients with SLE (n=95) and demographically matched healthy control participants (n=48) underwent cognitive testing using the 1-hour neuropsychiatric test battery recommended by the American College of Rheumatology for use in SLE and the MoCA. We used regression analyses to determine associations between MoCA and cognitive test scores. We assessed several MoCA cut-offs for predicting cognitive impairment in terms of sensitivity, specificity, positive predictive value and negative predictive value. Receiver operating curve analyses were used to determine the diagnostic accuracy of the MoCA cut-off thresholds.Results We found a significant correlation between MoCA score and 9 of the 10 cognitive endpoints studied (all p<0.001). Receiver operating curve analysis suggested that a MoCA cut-off of <27 had highest diagnostic accuracy across the cognitive impairment definitions (area under the curve 0.76–0.78). Using a screening cut-off of <28, the MoCA had sensitivity of 83%–94% and specificity of 46%–59%, depending on the impairment definition used.Conclusions The MoCA correlates strongly with cognitive test results in SLE and has sufficient sensitivity for use as a screening tool with a cut-off of <28 as the optimal threshold. This tool can be incorporated into clinical practice for screening for cognitive dysfunction in SLE.